2004
DOI: 10.1624/105812404x1725
|View full text |Cite
|
Sign up to set email alerts
|

Are There Long-Term Consequences of Pain in Newborn or Very Young Infants?

Abstract: Physiologic studies indicate that very early pain or stress experiences have more than immediate consequences for infants. Assessment and care of pain are complex subjects made even more complex and challenging when the individual experiencing pain is a very young infant. This review provides evidence that significant and long-lasting physiological consequences may follow painful insults in the very young, including changes in the central nervous system and changes in responsiveness of the neuroendocrine and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 43 publications
0
50
0
1
Order By: Relevance
“…This was constant with Page [38] who explore that immune function is another area impacted by early experiences with pain or stress and consistently shown in animal studies. The current study indicated that there was statistically significant relation between premature infants' behavioral state during needle painful events and their CRP weekly profile.…”
Section: Discussionmentioning
confidence: 81%
“…This was constant with Page [38] who explore that immune function is another area impacted by early experiences with pain or stress and consistently shown in animal studies. The current study indicated that there was statistically significant relation between premature infants' behavioral state during needle painful events and their CRP weekly profile.…”
Section: Discussionmentioning
confidence: 81%
“…The assessment and the care of pain are complex issues made even more challenging when the individual experiencing pain is a very young infant 42. Although several pharmacological and non-pharmacological therapies are available, information is not effectively translated into clinical practice 43 44.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that pain in the newborn period has consequences later in life, such as altered behavior, increased pain sensitivity and decreased function of the immune system [4,15,28]. To date neonatal pain research has mainly focused on acute and procedural pain.…”
Section: A Real Case Application To Chronic Pain In Neonates Definitionmentioning
confidence: 99%